Экономическая теория учебное пособие для вузов - Клюня В. Л. Владимир Леонидович; Новикова И. В. Ирина Васильевна; Зеленкевич М. Л. Марина Леонидовна; Ермалович Л. П.; Дакуко Л. И.; Максименко-Новохрост Т. В.; Новикова И. В. Марина Леонидовна (Минск, ТетраСистемс, 2001)
Авт. указ. на обороте тит. л.